CHARACTERISTICS OF THE PEAT SOIL Bacilllus sp. - Iman Hidayat (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
Twenty two strains of Bacillus species have been isolated from the peat soil of Tanjung Puting, Central Kalimantan. All strains devided into seventeen groups which characterized using morphology and biochemical tests. All strains have been tested for lipase, amylase, protease, cellulase, and phosphatase activity. Thirteen Bacillus isolates tested gave positif reaction for lipase activity. Bacillus AR 018 was the best isolate for amylase activity, Bacillus AR 001 and Bacillus AR 002 for protease activity, Bacillus AR 009 for cellulase activity. Only one isolate shows positive reaction for phosphatase activity, notably Bacillus AR 007.